(untitled) (Research, Society and Development, 2020)
To identify the factors associated with Burnout Syndrome in nursing professionals working in hospital care. Quantitative cross-sectional study conducted with 39 professionals that make up the nursing staff of a medium-sized hospital in the northwest region of Rio Grande do Sul / Brazil. Data collection occurred through the use of a self-administered structured questionnaire. Statistically associated with Burnout Syndrome were age and feeling of overload. Chronic stress related to the work environment directly reflects on workers’ health, thus causing pathological conditions resulting in serious diseases such as Burnout Syndrome.